Disruption of Thalamocortical Connectivity in Spastic Cerebral Palsy: A Probabilistic Tractography Study - Mukhtar, Siti Fatimah; Ahmad, Asma Hayati; Simok, Anna Alicia; Abdullah, Jafri Malin; Abdullah, Aimi Nadhiah; Zabri, Siti Hajar; Ahmad Kamil, Wan Sarah Wan; Yaacob, Najib Majdi; Sapiai, Nur Asma; Mohd Ismail, Zul Izhar (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Objectives: This study aimed to investigate the probabilistic connectivity between the thalamus and motor areas of the cerebral cortex in spastic cerebral palsy (SCP). We explored the integrity of motor tracts between the thalamus and cerebral cortex by quantifying the thalamic probabilistic connectivity with motor cortices (namely primary motor cortex, supplementary motor area, and premotor cortex) in SCP using diffusion MRI. The current study also parcellated the thalamus according to its connectivity to the three motor cortices in healthy control and SCP. Methods: Probabilistic tractography was performed on secondary diffusion MRI data of eight SCP patients (mean age 11.9 years old) and ten healthy controls. The connection probability index, an indirect indicator of white matter integrity, was measured between the thalamus to three areas of the motor cortex; primary motor, premotor and supplementary motor. The thalamus was further parcellated according to its connection probability with the motor cortices. Results: The pattern of thalamocortical connectivity in cerebral palsy was found to be varied and mainly complied with the patient's clinical presentation. In comparison with controls, the SCP patients showed either lower or higher connection probabilities to the motor cortices. A striking feature of thalamic parcellation in SCP was the presence of a cluster with a positive connection to the supplementary motor area. Conclusion: Our findings suggest that the thalamocortical connectivity in SCP was different from healthy individuals and largely follows the clinical manifestation. There was also evidence of neuroplasticity serving as a compensatory mechanism for the motor deficit in patients with SCP.